Human-environment interactions in rural and agricultural communities: identifying opportunities for sustainability efforts using quantitative, qualitative, and GIS methods - Fischer, Amariah (Kansas State University, 2024)
The United States agriculture industry, especially in the Midwest, is expected to be adversely impacted by the consequences of climate change, with temperature and precipitation changes making sufficient crop production exceedingly difficult to achieve. Further, the agriculture industry is also a significant contributor to climate change and faces a rising global population with increased food demands. The combination of these circumstances creates a context in which members of agriculture and food systems must adapt to a changing climate to increase food production while simultaneously rethinking traditional approaches to agriculture to mitigate contributions to climate change. This makes the study of agricultural sustainability, and the sustainability of the many rural communities that rely on agriculture, essential for the future of our planet. However, given the complex nature of problems in agricultural and rural sustainability, solutions often require an interdisciplinary approach and the consideration and integration of both human and natural systems. The goal of this research was to contribute to agriculture and rural sustainability by conducting three different research projects that each focused on an area of agricultural or rural sustainability. In chapter three, we investigate how the physical water environment shapes water conservation norms among farmers in the High Plains-Ogallala Aquifer, the largest source of groundwater in the United States. These questions were approached in terms of cultural adaptation to the physical environment, comparing irrigators with dryland farmers using survey and environmental data. I used the values-beliefs-norms (VBN) framework to develop a conceptual model to integrate the physical water context as an exogenous explanation of water conservation norms. Grouped simultaneous equation models indicate a limited form of cultural adaptation in the region that, from a biological perspective, could be considered evidence of mal-adaptation. Both irrigators and dryland operators in more water-rich environments hold stronger water conservation norms and those in more arid environments hold weaker water conservation norms. For irrigators, the relationship between the water context and norms is partially mediated by worldviews where irrigators in more water scarce contexts tend to hold more ecocentric worldviews that motivate conservation. The findings suggest the importance of considering farmers’ practices (dryland farming or irrigation) and their places (physical water context) in shaping their decision-making in an integrated socio-ecological context. In chapter four, measures of rurality were investigated. Government agencies and researchers often rely on quantitative measures to map where rural places are and who belongs to rural communities. To better understand the consistency, or lack thereof, across different quantitative rural measures, we compare four common measures applied at the county level for the contiguous United States. My purpose was to (1) quantify and map the degree of rural agreement among these selected rural measures and (2) describe key characteristics of counties classified as rural through urban. Comparing different measures yielded little agreement on rural places with consensus achieved for only 114 of 3,108 counties (3.7%). County variables contributing to good separability in rural to urban classifications included remoteness, population density, percent of the population aged 65 and over, employment in the agricultural sector, and both developed and grassland landcover. Closer examination of the underlying characteristics of the 114 consensus rural counties provides an opportunity to reflect on the nature of popular rural measures and the variables they use. If these counties are not representative of how researchers conceptualize “rural” across US regions, it is motivation for working toward new and/or spatially adaptive rural measures that better represent the communities that policy and research intends to help. In chapter five, the process of regenerative agriculture adoption was examined. To address the negative environmental impact of industrial agricultural practices, research has been dedicated to the adoption of regenerative agriculture (RA) as it has been shown to reduce agriculture’s overall contribution to climate change and better prepare farming operations for future changes in climate. The adoption of RA practices has been linked to systems thinking, with farmers employing regenerative farming practices reporting higher engagement with systems thinking. This study interrogates this relationship further by examining how industrial and regenerative farmers demonstrate systems thinking skills. To do this, sixteen cognitive maps of individual farm systems were collected through qualitative interviews with farmers in central Kansas. These cognitive maps were then used to compare systems thinking skills across farmers employing practices along the spectrum of industrial to regenerative. Results showed that regenerative farmers demonstrated more developed systems thinking skills when compared to industrial farmers. Further, the cognitive maps of regenerative farmers prioritized internal and ecological farm factors, particularly soil health, while those of industrial farmers emphasized external and human-driven farm factors.
Keywords: Rural measures; Groundwater conservation; Regenerative agriculture